Association of omega-6 polyunsaturated fatty acids with blood pressure: A systematic review and meta-analysis of observational studies. Issue 14 (30th May 2023) - Hajihashemi, Parisa; Feizi, Awat; Heidari, Zahra; Haghighatdoost, Fahimeh
Abstract: Objectives: This systematic review and meta-analysis aimed at summarizing earlier findings on the association of n-6 PUFAs levels in diets or blood with blood pressure. Methods: PubMed/Medline, Scopus, and Web of Science were searched for observational studies. Publications with data on the risk of hypertension, or the correlation between n-6 PUFAs or mean values of serum n-6 PUFAs levels in normotensive and hypertensive were included. Results: Twenty-two studies (16 cross-sectional studies, 5 cohorts and one case-control) were eligible. Combining 14 extracted effect sizes showed that higher circulatory/dietary n-6 PUFAs tended to be associated with 10% lower risk of HTN (95% CI: 0.81, 1.00), whereas combining 23 effect sizes illustrated no difference in circulatory/dietary n-6 PUFAs mean levels between normotensive and hypertensive subjects. According to subgroup analysis based on fatty acid types, total n-6 PUFAs (OR = 0.82, 95% CI: 0.70, 0.97) and linoleic acid (OR = 0.56, 95% CI: 0.39, 0.82) were inversely related to the risk of HTN. Circulatory/dietary n-6 PUFAs were correlated neither with systolic nor with diastolic blood pressure. Conclusions: Higher circulatory/dietary n-6 PUFAs tend to be associated with lower odds of HTN. Particularly, total n-6 PUFAs and linoleic acid were associated with lower risk of HTN.